2008
DOI: 10.1017/s146342360800087x
|View full text |Cite
|
Sign up to set email alerts
|

Can social prescribing provide the missing link?

Abstract: Background: The voluntary sector has long been recognised as making an important contribution to individual and community health. In the UK, however, the links between primary health care services and the voluntary and community sector are often underdeveloped. Social prescribing is an innovative approach, which aims to promote the use of the voluntary sector within primary health care. Social prescribing involves the creation of referral pathways that allow primary health care patients with non-clinical needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
152
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 22 publications
1
152
0
1
Order By: Relevance
“…7 Other research has also reported difficulty with recruitment to social prescribing schemes. 5,11 This is despite the markers for suitability (listed previously) being very common.…”
Section: Engagement Of Gps and Other Primary Care Health Professionalsmentioning
confidence: 99%
See 3 more Smart Citations
“…7 Other research has also reported difficulty with recruitment to social prescribing schemes. 5,11 This is despite the markers for suitability (listed previously) being very common.…”
Section: Engagement Of Gps and Other Primary Care Health Professionalsmentioning
confidence: 99%
“…The most favoured among existing schemes involves the use of a 'facilitator' (or referral agent or navigator) coupled with personal support (often a volunteer) for the patient in actually taking up social opportunities. [3][4][5] The facilitator is employed to act as a bridge between primary care professionals and the panoply of social opportunities. It is a challenging role requiring good listening skills and the ability to relate in an inspiring way to health professionals, the wide variety of people in the third sector and, of course, the patient who has been referred.…”
Section: What Is the Process Of Making A Social Prescription?mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, voluntary organisations and charities as third sector organisations are increasing their role in providing an adjunct to primary care services (Coid, Williams, & Crombie, 2003;Secretary of State for Health, 2006). Social prescribing, also referred to as community referral, has gained considerable attention in recent years (Husk et al, 2016;Kilgarriff-Foster & O'Cathain, 2015;Mossabir, Morris, Kennedy, Blickem, & Rogers, 2015;South, Higgins, Woodall & White, 2008). Social prescribing is defined as: "A mechanism…”
Section: Introductionmentioning
confidence: 99%